Analisis Penggunaan Teknik Interaktif Buku Cerita Bergambar Bahaya Gula Minuman Kemasan pada Anak - Salsabilah, Audyva (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study examines how interactive storybooks can help children aged 7 to 9 years learn about the dangers of excessive sugar consumption in packaged drinks. The book is designed with interactive techniques such as pop-up, pull-the-tab, and lift-the-flap to enhance the effectiveness of learning for children. Each mechanical method is aimed at capturing the children’s attention and delivering an educational message in an engaging and easy-to-understand way. The results show that the pull-the-tab technique was the most commonly used because of its ease of use and effectiveness in illustrating gradual changes. This technique allows children to visually see how excessive sugar consumption affects the body through changes that occur when they pull the tab on the book. Additionally, the use of pop-up and lift-the-flap methods provides a visually and physically engaging experience, which makes children more involved in the learning process. Based on the findings, interactive storybooks have proven to be a highly effective learning tool for educating children about important health issues. Therefore, book developers are encouraged to continue innovating by incorporating various interactive methods, such as adapting the books into digital formats. By doing so, a broader and more effective educational impact can be achieved, allowing children to learn in a fun, interactive, and easily accessible way.